Peran guru sebagai role model dalam pembentukan karakter siswa - Ummi Zakiyah Darojat; Romadhon; Erna Yayuk (Yayasan Baru Haji Samsudin, 2026)
Education has a strategic role in shaping human resources that are not only academically excellent but also possess strong character values. Teachers act as role models in the character-building process of students through exemplary behavior, guidance, and motivation. This study aims to analyze the role of teachers as role models in character formation, the process of character development through exemplary practices, as well as the supporting and inhibiting factors involved. This research employed a qualitative approach using a literature study method on seven relevant scientific articles published between 2021 and 2026. The findings indicate that teachers have multidimensional roles as exemplars, mentors, and motivators. The process of character formation occurs through modeling mechanisms, namely observation, imitation, internalization, and habituation. Supporting factors include a conducive school environment, collaboration with parents, and the integration of character values into learning activities. Meanwhile, inhibiting factors include teachers’ lack of consistency, external environmental influences, and the gap between theory and practice. Therefore, the role of teachers as role models is a key factor in the success of character education.